Newborn Readmissions to Slovenian Children's Hospitals in One Summer Month and One Autumn Month: A Retrospective Study - Tina Perme; Andrejka Škafar Cerkvenik; Štefan Grosek (Pediatrics and Neonatology, 2016)
With the shortening length of stay of newborns in hospitals after birth, concerns have been raised about the possible rise in readmission rates. In Slovenia, where the normal length of stay is 3 days, no data on readmissions were available. We sought to determine the frequency and causes for readmissions. Methods: We conducted a retrospective study on all newborns readmitted to Slovenian children's hospitals and wards in June 2012 and November 2012. We obtained basic demographic data for newborns and mothers, analyzed the frequency of diagnoses, and compared the duration of treatment between summer months and autumn months. Results: The proportion of readmissions in June 2012 and November 2012 was 6% and 5.9%, respectively. Around 10% more boys were readmitted in June 2012 and November 2012. In June 2012, the mean age was 12.2 days, and the mean birth weight was 3444 g. In November, the mean age was 10.5 days, and the mean birth weight was 3271 g. Around 50% of mothers were primiparous, and their mean age was around 31 years. Most received > 10 prenatal check-ups and participated in a prenatal class. The most common diagnosis in June 2012 and November 2012 was jaundice. The duration of treatment did not statistically significantly differ between summer months and autumn months, but it was associated with the admission diagnosis and infants' characteristics. Conclusion: Our study showed that the readmission rate in Slovenia was much higher than in some other developed countries. Prospective studies are needed to further confirm the findings and highlight the possible causes for this observation.